2018
DOI: 10.1177/1524838018756121
|View full text |Cite
|
Sign up to set email alerts
|

Widening the Lens: An Ecological Review of Campus Sexual Assault

Abstract: Varying prevalence rates of sexual violence across colleges and universities indicate the need to understand institutional factors underlying such variation; however, research often focuses exclusively on individual risk and protective factors, which both under theorizes and under explains the phenomenon of campus sexual assault. In this review, we propose that broadening to include campus- and contextual-level factors is necessary to fully explain campus sexual assault. Using an ecological approach, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(169 citation statements)
references
References 79 publications
2
141
0
1
Order By: Relevance
“…Despite the horrifying extent of college sexual assault and the broad deleterious consequences, little is known about how variations in campus resources, demographics, and agency collaboration affects CSA prevention, detection, and response efforts (DeLong et al, 2018; Moylan & Javorka, 2020). The field needs this contextual information in order to create effective, efficient individual and institutional interventions to protect students in higher education (Banyard, 2014; DeLong et al, 2018; DeMatteo et al, 2015; McMahon et al, 2019; Mellins et al, 2017; Streng & Kamimura, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the horrifying extent of college sexual assault and the broad deleterious consequences, little is known about how variations in campus resources, demographics, and agency collaboration affects CSA prevention, detection, and response efforts (DeLong et al, 2018; Moylan & Javorka, 2020). The field needs this contextual information in order to create effective, efficient individual and institutional interventions to protect students in higher education (Banyard, 2014; DeLong et al, 2018; DeMatteo et al, 2015; McMahon et al, 2019; Mellins et al, 2017; Streng & Kamimura, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to policy and procedure, more comprehensive campus sexual assault (CSA) policies (as defined by the 2014 Checklist for Campus Sexual Misconduct Policies; White House Task Force to Protect Students From Sexual Assault, 2014) are associated with lower CSA rates (DeLong et al, 2018) and are critical to the prevention of sexual violence (Moylan & Javorka, 2020; Richards, 2016). Currently, there is limited evidence surrounding the efficacy of individual CSA perpetration prevention programs (DeGue, 2014; DeGue et al, 2014), with the best evidence thus far supporting interventions that train bystanders to intervene.…”
mentioning
confidence: 99%
“…Understanding and solving the problem of campus sexual assault will require a focus beyond an examination of the prevalence of sexual violence. Research is needed to examine the implementation and impact of institutional, state, and federal policy (Moylan & Javorka, ). While some policy efforts aim to increase options available to sexual assault survivors (e.g., expanding victim advocacy services), others may reduce survivors’ disclosure options and choices (Holland et al., ; Richards & Kafonek, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that campus personnel involved in the administration of sexual assault policy (e.g., victim advocates, Title IX coordinators) expressed concern that a state law requiring universities to report assaults to the police could take control away from survivors and decrease their ability to protect survivors’ confidentiality (Brubaker & Mancini, ). Institutional responses to sexual assault vary across campus contexts, and to adequately address sexual violence, it is essential to consider how the people within these institutions perceive and experience sexual assault policy (Moylan & Javorka, ). Responsible Employees’ perceptions of their reporting requirements can affect their work lives and relationships with students in significant ways.…”
Section: Ra Roles Under Federal and Institutional Policymentioning
confidence: 99%
“…An analysis of the background literature revealed three primary conclusions about the existing knowledge. First, the research indicated consistency in the prevalence, characteristics, and elements of sexual assault in higher education stating that 20% to 25% of college women experience some form of sexual assault (Bureau of Justice Statistics, 2014;Cantalupo, 2009;Krebs et al, 2016;Moylan & Javorka, 2020). Despite the high rates of sexual assault, it is underreported across college and university campuses out of shame, fear, or self-blame (Cantalupo, 2009; End Rape on Campus, 2016).…”
Section: Discussion In Relation To the Literature Reviewmentioning
confidence: 99%